Entrega de ropa, víveres no perecibles y agua a los damnificados del cantón Las Naves. - Llivi Ruilova, Danny Vicente (2024)
The Spirit of Solidarity was present through the delivery of clothing, non-perishable food and water; donated by teachers and students of 1, 2, 4, 5, 6 and 7 cycles of the Nursing degree, to help the victims of the Las Naves canton, who as a result of the “El Niño” Phenomenon, have lost everything.